Prostetic Rehabilitation of an Eye Globe: Case Report - Goiato, Marcelo Coelho [UNESP]; Dos Santos, Daniela Micheline [UNESP]; de Sousa Ervolino, Isabela Caroline [UNESP]; Brunetto, Juliana Lujan [UNESP]; de Magalhaes Bertoz, Andre Pinheiro [UNESP]; de Moraes Melo Neto, Clovis Lamartine [UNESP] (ScopeMed, 2019)
Introduction: The lack of an eye has an immediate and long-term impact on a patient's life. Aim: The aim of this study is to show a case of prosthetic rehabilitation of an eyeball. Case report: Male patient, 60 years old, sought care at the Oral Oncology Center of the São Paulo State University Júlio de Mesquita Filho, for the rehabilitation of the orbital cavity with an acrylic eye prosthesis. This prosthesis was made with thermopolymerizable acrylic resin and hand painted iris with oil paint on cardboard. The prosthesis was installed after finishing and polishing and the hygiene and general care instructions were explained. Conclusion: In the present case, the patient was satisfied with the aesthetics and comfort of the prosthesis, which demonstrates the success of the treatment.
Keywords: Enophthalmos; Glaucoma; Ocular Prosthesis